L’officier de police, le checkpoint et l’interrogatoire : les spatialités des performances sécuritaires dans le centre-ville du Caire - Laura Monfleur (L’Année du Maghreb)
The strengthening of the security apparatus is one of the elements of the authoritarian takeover in post-revolutionary Egypt in 2011. Analyzed institutionally in works in sociology and political science, we assume that this takeover can also be analyzed from below, at street level. In this article, we propose to analyze the practices of the forces of law and order according to their spatialities in downtown Cairo. Drawing on interactionist sociology and a geography attentive to the sensorial dimension of spaces, these spatialities are linked to the notion of security performance. Through this notion, the aim is to account for the way in which police practices and devices appropriate urban spaces, which are then constituted as issues of securitization, and, in return, construct the spaces of the street and square as spaces where a security spatial order is imposed. We also shift the focus from analyses of police practices often carried out in the context of protests to the way in which security performance manifests itself on a daily basis. They certainly contribute to anticipating protest practices, but they also impose constraints on the everyday practices and perceptions of users of urban spaces. These constraints vary according to space, time, the role of the police and the identity displayed or assigned to city dwellers. Three spatial dimensions of policing are analyzed in turn: the location of law enforcement actors, the physical infrastructures that occupy space and filter mobility, and the spatial representations of police officers. The bodily performance of police officers is reflected in their uniforms, gestures and postures, which make them visible and contribute to the distrust and suspicion of users. However, these bodily performances vary according to the type of police actor, testifying to the fact that the security actors attached to the Ministry of the Interior are not a monolithic block. Checkpoints produce a security landscape whose perceptions vary between tranquility and familiarity on the one hand, and insecurity and uncertainty on the other. The first type corresponds mainly to checkpoints in front of places of worship: daily interaction is greater with these police officers, the spatial hold of the police presence is less constraining and is only experienced when visiting places of worship, the reason for their presence linked to the terrorist risk seems more legitimate. The second type corresponds to checkpoints around political institutions and at times of heightened security to prevent demonstrations: the daily distance is greater with the police officers present there, their spatial hold more restricts mobility and sometimes imposes detours, and their role is deemed less legitimate and insecure. Thus, the constraints linked to security performances vary according to their role, place and time. Finally, discursive performance is also a feature of police encounters. Their frequency and outcome depend on certain characteristics of city dwellers.On a broader scale, this article shows how the spatial and political context of the city center explains its security performance: the presence of institutions to be protected, historical sites of protests, a project to attract tourists. In turn, security performance constructs downtown Cairo as a sensitive zone where police presence, checkpoints and interrogations are all reminders of the social order, a way of telling everyone their place and who has coercive power, but also of a spatial order, a way of signifying to whom downtown belongs.This research is based on various field surveys conducted in Cairo in 2015 and then between 2019 and 2021. Observations of urban spaces in Wast al-Balad enabled systematic surveys to be carried out and a map of security infrastructures and law enforcement agencies to be produced. Around 60 interviews were conducted with residents and users of the town center. These interviews focused primarily on day-to-day practices - getting around, shopping, working, relaxing, meeting people - and also provided an opportunity to work on how the police are perceived and to collect micro-stories of typical situations with police officers.